Development Of Microsatellite Markers And Genetic Diversity Assessment Of Kempas (Koompassia Malaccensis) In Peninsular Malaysia - Lee, Chai Ting (2009)
A total of 24 novel microsatellite markers have been successfully isolated and characterised in an important tropical timber species of the family Leguminosae, Koompassia malaccensis, locally known as kempas. The microsatellite primers were designed from a genomic library enriched for dinucleotide (CT) repeats and subsequently screened on 24 samples from a natural population. In general, these microsatellite markers are highly polymorphic (mean number of alleles per locus, Aa = 6.84; average gene diversity, He = 0.692), with two loci found to deviate significantly from Hardy-Weinberg equilibrium (p < 0.05). The utility of these microsatellite markers were tested across 13 leguminous timber tree species and the highest transferability was found with K. excelsa, the only species of the same genus tested, followed by Dialium platysepalum of the same subtribe, Dialiinae. The amplification success appeared to be inversely associated with the phylogenetic distance, in particular up to the subtribal levels. Four of the microsatellite loci were used to study the mating system of K. malaccensis, based on a fruiting season at the Semangkok Forest Reserve in year 2005.